Протидія торгівлі людьми: проблеми міжнародно-правового врегулювання - Путінцев, І. О. (ХНУРЕ, 2022)
The article deals with the problems of international legal regulation of combating human trafficking. It is argued that human trafficking is a modern form of slavery, accompanied by the most cynical and cruel violations of human rights. A person becomes the object of a transaction, property rights apply to him, like a commodity. People are forcibly, and more often fraudulently, transported across state borders, forced to work, driven into debt bondage, deprived of freedom of movement, and subjected to physical, mental, and sexual violence. Most of the victims of human trafficking are women and children who, against the backdrop of a growing sex industry, are engaged in forced prostitution.
Keywords: протидія торгівлі людьми